Cat’s Monitoring and Feeding Systems via Internet of Things (IoT) - Mohd Rasyidi, Nasrin Hannani; Mohd Zin, Rosnah (Evolution in Electrical and Electronic Engineering, 2021)
A cat (Felis cats) is a small carnivorous mammal domestic animal and more like a household child. Thus, to keep a good emotional bond between the cat and its owner, the cat keeper needs to monitor and feed the cat regularly even he or she has difficulty go to outstation. To assist the cat keeper, a monitoring and feeding system for the cat should be created to aid in delivering the cat’s food automatically or manually via the Internet of Things (IoT) in a unitary portable cat feeder with two removable storage containers that include feeding food and drinking part. The method of the project uses the concept of IoT. From the controller devices like NodeMCU ESP 32 and ESP 32 camera module, application by using Blynk Application, and last to the collecting sensor data via MATLAB ThingSpeak, used the concept of IoT because they connect with a wide range of Wi-Fi network. The contribution from the IoT system will make this technology reliable and easy for the user to use. These proposed systems are believed to monitor and feed the cat efficiently without presented by its owner, and finally helping the cat keeper keep a good emotional bond with the cat once completed.